Analisis Pengendalian Kualitas Menggunakan Metode QC Seven Tools pada Produk X di PT DOM - Bathin Malandri, Yoga; Safariyani, Eva; Divala Zahra, Shakila; Alfanadim, Andraya (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
The Production Department at PT DOM faces a high defect rate in the chain model x. This study aims to identify the types of defects, analyze their root causes, and provide improvement recommendations to reduce defects. The method used in this research is the Seven Tools approach, which includes Check Sheet, Histogram, Pareto Diagram, Fishbone Diagram, Scatter Diagram, and Control Chart. The results indicate 14 major types of defects, with outer plate endless reversed, assy no riveting, and pin black (adhesion) being the most dominant. The Fishbone Diagram analysis identifies the primary causes of defects as stemming from human factors, machinery, methods, materials, and the environment. The Control Chart shows that the production process remains within control limits, but improvements are needed to enhance efficiency. Recommended improvements include operator training, enhanced quality supervision, implementation of preventive maintenance, and strict analysis of raw material suppliers. Implementing these strategies is expected to reduce defect rates and improve the quality of the chain model x. Keywords: Control Chart, Defect, Fishbone Diagram, Quality Control, Seven Tools